QUARK MEAN-FIELD THEORY AND CONSISTENCY WITH NUCLEAR-MATTER - Dey, J.; Tomio, L.; Dey, M.; Frederico, T. (American Physical Soc, 1991)
1/N(c) expansion in QCD (with N(c) the number of colors) suggests using a potential from meson sector (e.g., Richardson) for baryons. For light quarks a sigma-field has to be introduced to ensure chiral symmetry breaking (chi-SB). It is found that nuclear matter properties can be used to pin down the chi-SB modeling. All masses, M(N), m-sigma, m-omega, are found to scale with density. The equations are solved self-consistently.